Buddhist Symbols and Imageries - Kochumuttom, Thomas (Journal of Dharma, 1984)
In general Buddhism has always distrusted the ability of ordinary language adequately to express truths about ultimate realities, and hence has taken frequent recourse to symbols and imageries to deal with them. Such symbols and imageries in Buddhism may be classified into five groups : doctrinal, mythical, cultic, iconographic and conventional. In the present article we shall make a survey of these five groups of Buddhist symbols and imageries.